Case report: Insulinomatosis: description of four sporadic cases and review of the literature - Lourenço, Delmar Muniz; Corrêa-Giannella, Maria Lucia; Siqueira, Sheila Aparecida Coelho; Nery, Marcia; Ribeiro, Flavio Galvão; Quedas, Elizangela Pereira de Souza; Rocha, Manoel de Souza; Nascimento, Ramon Marcelino do; Pereira, Maria Adelaide Albergaria (Frontiers in Endocrinology, 2024)
The best-known etiologies of hyperinsulinemic hypoglycemia are insulinoma, noninsulinoma pancreatogenous hypoglycemic syndrome, autoimmune processes, and factitious hypoglycemia. In 2009 a disease, not associated with classic genetic syndromes and characterized by the presence of multiple pancreatic lesions, was described, and named insulinomatosis. We present the clinical and pathologic features of four patients with the diagnosis of insulinomatosis, aggregated new clinical data, reviewed extensively the literature, and illustrated the nature and evolution of this recently recognized disease. One of our patients had isolated (without fasting hypoglycemia) postprandial hypoglycemia, an occurrence not previously reported in the literature. Furthermore, we reported the second case presenting malignant disease. All of them had persistent/recurrent hypoglycemia after first surgery even with pathology confirming the presence of a positive-insulin neuroendocrine tumor. Including literature review, 27 sporadic insulinomatosis cases were compiled. All of them had episodes of fasting hypoglycemia except one of our patients. Only two patients had malignant disease, one of them from our series. The suspicion of insulinomatosis can be raised before surgery in patients without genetic syndromes, with multiple tumors in the topographic investigation and in those who had persistence or recurrence of the hypoglycemia after surgical removal of one or more tumors. The definitive diagnosis is established by histology and immunohistochemistry and requires examination of the “macroscopically normal pancreas". Our cases series reinforce the marked predominance in women, the high frequency of recurrent hypoglycemia and, consequently, a definitive poor response to the usual surgical treatment.